2010
DOI: 10.1039/b923013k
|View full text |Cite
|
Sign up to set email alerts
|

Unusual bridging of three nitrates with two bridgehead protons in an octaprotonated azacryptand

Abstract: Structural analysis of the nitrate complex of a thiophene-based azacryptand suggests that three nitrates are bridged with two bridgehead protons which play the topological role of two transition metal ions in a classical Werner type coordination complex bridging three anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The highest changes were obtained for the protons H b and H c that are connected with the tertiary nitrogens. This observation suggested the possible interaction of central charged nitrogen atoms21 in binding of the anion that was further confirmed by the structural analysis of the sulfate complex. In addition, aromatic protons of the p -xylyl subunits were also shifted and could be due to the spatial proximity of the corresponding protons to the negatively charged anion in the complex.…”
supporting
confidence: 57%
“…The highest changes were obtained for the protons H b and H c that are connected with the tertiary nitrogens. This observation suggested the possible interaction of central charged nitrogen atoms21 in binding of the anion that was further confirmed by the structural analysis of the sulfate complex. In addition, aromatic protons of the p -xylyl subunits were also shifted and could be due to the spatial proximity of the corresponding protons to the negatively charged anion in the complex.…”
supporting
confidence: 57%
“…The absence of an anion inside the cavity makes L favorable for hosting the water molecules. The distance between the bridgehead nitrogen sites is longer (7.891 Å) than the corresponding distance in the chloride (6.096(4) Å)13a or nitrate (5.528(6) Å)13b complex, where the internally bound anion brings the two bridgehead amines closer through electrostatic interactions. The geometry of the hybrid pentamer is similar to the cyclic pentamer observed in a lattice of hydrated trans -bis(4-pyridyl)ethylene dioxide 21a.…”
mentioning
confidence: 88%
“…We recently reported that the bicyclic receptor L effectively binds chloride[13a] and nitrate[13b] ions in aqueous solution through the protonated bridgehead amines. While one chloride was found to be encapsulated linearly within the cavity, three nitrates were bridged in L forming a [NH(NO 3 ) 3 HN] + motif in the solid state.…”
mentioning
confidence: 99%
“…The choice of hexatosylated H 6 L·6Ts salt in the NMR titration was due to assumption that the bulky tosylate groups would remain outside the cavity and would have poor interactions with the ligands. 45,46 As shown in Figure 1, the addition of one equivalent of respective anion to H 6 L(Ts) 6 resulted in a significant downfield shift of NCH 2 C H 2 (b) proton for all anions, allowing us to evaluate the binding constants by NMR titrations. The other aliphatic protons of NC H 2 CH 2 (c) slightly shifted downfield only in the case of nitrate.…”
Section: Resultsmentioning
confidence: 99%
“…45 Upon further investigation on nitrate anions, it was shown to complex three nitrates in solid state. 46 In particular, the thiophene rings in the bridging chains can act as better electron-withdrawing groups than the corresponding aromatic analogues, thereby enhancing hydrogen bonding ability of the protons on ammonium groups. This assumption was further supported by the electrostatic potential surfaces of L calculated at the B3LYP/6-311G(d,p) level of theory (discussed later), showing the highest electron density on thiophene groups (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%